O direito à educação dos presos no Brasil: perspectivas do direito ao acesso à educação no sistema prisional e a atual normatização processual e de execução penal - Ramos Netto, Justino de Mattos (2006)
This present study aims to look at the importance of the right to education of prisoners in relation to the criminal procedural norms granted by the Brazilian constitution which guarantees universal access to basic education. The objective of this study is to demonstrate that education of prisoners make them less likely to re-offend because it facilitates their re-integration to their community at the end of their prison sentences. As a consequence, the whole society can benefit from the implementation of the right of education of prisoners. The method of study employed involved the analysis of other research and references addressing the problem of education of prisoners in Brazil, the analysis of the constitutional rules and of criminal proceedings in the past and present time, giving a historical view of the evolution of criminal procedural laws in Brazil. Moreover, this research investigates some models of public administration which put into practice education polices and techniques as a means to integrate prisoners in society. Finally, it highlights the need to support the agents who will be directly dealing with the education of prisoners and offers alternatives